Peran Orang Tua Terhadap Keaktifan Anak Sekolah Minggu Dalam Ibadah Anak Sekolah Minggu Di Jemaat GMIM Baitani Kopiwangker Wilayah Langowan IV - Sembel, Gratia Annastasia; Manumpil, Michael C. A. (Educatio Christi, 2021)
This journal discusses how the role of parents in children's activity in Sunday school children's worship and how parents can educate their children properly and correctly. Parents' upbringing is so influential on children, what has been taught, exemplified to them will be done in children's lives. For a child, parents have a very important role in the child's life in the responsibility and obligation have a very important role, in worship for a child is very important in building the spiritual growth and faith of children. Motivating children to be diligent in worship is a task for parents who must teach their children from a young age to always know God in their life journey. To see that, the analysis in the preparation of this article uses qualitative methods and approaches in the form of observations and interviews. That way, a relevant role will be found for parents in educating their children.